Implementation of Love-Based Curriculum: An Islamic Education Perspective - Burhanudin, Burhanudin (IAIN Manado, 2025)
The phenomenon of moral degradation, empathy crisis, and educational orientation that overemphasizes cognitive aspects gives rise to the need for a new approach in curriculum development. This study aims to explore the implementation of a love-based curriculum from an Islamic educational perspective as an effort to present a humanistic, spiritual, and character-oriented learning process. The research method employed is library research, which involves examining the literature related to the Qur'an, Hadith, the thoughts of classical and contemporary Islamic educational figures, and modern academic theories. The results of the study indicate that a love-based curriculum integrates intellectual, emotional, and spiritual dimensions, with the main principles of rahmatan lil-'alamin (blessing for all the universe), compassion, etiquette, and ukhuwah (brotherhood) as its core. Its implementation can be seen in the planning of curriculum objectives, dialogic learning strategies, and evaluations that emphasize the affective and spiritual aspects. This research is significant because it offers an alternative paradigm for developing an Islamic education curriculum that is relevant to contemporary needs and grounded in divine values.